Nigerian Oil and Gas Industry: Laws, Policies, and Institutions - Usman, Adamu Kyuka (Malthouse Press Limited, Nigeria, 2017)
Though predominantly on oil and gas law, this is nonetheless a veritable Reference Book on the oil and gas industry in Nigeria. It places before anyone interested in the oil and gas industry basic and critical oil and gas issues not in common circulation in existing texts on the subject. The book is arranged in such a chronological order, like reference books and dictionaries tend to be, that a lay person in going through it would now know how oil is explored and found, how oil fields may be onshore and offshore, how oil blocs are bidded for, how oil is drilled, including associated gas deposits, among others. The transportation of oil and gas, storage of oil and gas, refining of oil and processing of gas, marketing of oil and gas, the impact of oil and gas exploration, production and revenues on the Nigerian environment, politics and economy and a myriad of other issues are comprehensively covered. The book should prove most useful to the lawyer, petroleum geologist, petroleum engineer, policy makers, investors, local and international development agencies and bodies, lecturers and students specialising in wide ranging subjects as economics, development studies, engineering, management, public administration, insurance, marketing, accounting and finance.